Leisure for Peace? Revisiting the Tourism-Peace Nexus - Okoli, Al Chukwuma; Alumona, Ikenna Mike (Faculdade de Filosofia e Ciências, 2020)
Tourism is an important aspect of the contemporary international commerce. It accounts for a significant share of the foreign exchange of many nations, especially those with a thriving tourism sector. While scholarly works abound on the economic, cultural and social values of tourism, there has been a debate as regards the utility of tourism as an enabler for peace. This paper interrogates the pacific import of international tourism against the backdrop of the growing significance of the tourism sector globally. By way of a qualitative analysis of secondary data, anchored on the theory of internationalism, the paper interrogates the tourism-peace nexus in the light of emerging insights, positing that international tourism holds potentials that could be leveraged towards promoting international peace and stability.     Recebido em: março/2019 Aprovado em: janeiro/2020.